METHODS FOR DEVELOPING GRAMMATICAL COMPETENCE IN B1 LEVEL STUDENTS (International journal of artificial intelligence, 2026)
This article examines effective methods for developing grammatical competence in B1 level English as a Foreign Language (EFL) students. Grammatical competence is a core component of communicative competence and plays a crucial role in enabling learners to produce accurate and meaningful language. At the B1 level, learners are expected to use a range of grammatical structures with a reasonable degree of control in both spoken and written communication. The study analyzes theoretical perspectives on grammar teaching and explores practical, learner-centered methods such as communicative grammar instruction, task-based learning, inductive and deductive approaches, contextualized grammar teaching, and the use of formative assessment. The article follows the IMRAD structure and aims to provide methodological guidance for English language teachers working with intermediate-level learners.